Impacts of Seagrass on Benthic Microalgae and Phytoplankton Communities in an Experimentally Warmed Coral Reef Mesocosm - Tew, Kwee Siong; Kuo, Jimmy; Cheng, Jing-O; Ko, Fung-Chi; Meng, Pei-Jie; Mayfield, Anderson B.; Liu, Pi-Jen (Frontiers in Marine Science, 2021)
The effects of seagrass on microalgal assemblages under experimentally elevated temperatures (28°C) and CO 2 partial pressures (pCO 2 ; 800 μatm) were examined using coral reef mesocosms. Concentrations of nitrate, ammonium, and benthic microalgal chlorophyll a (chl-a) were significantly higher in seagrass mesocosms, whereas phytoplankton chl-a concentrations were similar between seagrass and seagrass-free control mesocosms. In the seagrass group, fewer parasitic dinoflagellate OTUs (e.g., Syndiniales) were found in the benthic microalgal community though more symbiotic dinoflagellates (e.g., Cladocopium spp.) were quantified in the phytoplankton community. Our results suggest that, under ocean acidification conditions, the presence of seagrass nearby coral reefs may (1) enhance benthic primary productivity, (2) decrease parasitic dinoflagellate abundance, and (3) possibly increase the presence of symbiotic dinoflagellates.